Japan, China and the modern world economy : - Moulder, Frances V. (Cambridge University Press, 1977)
This book introduce about economy and society in Ch'ing China and Tokugawa Japan. China and Japan in the nineteeth-century. Incorporation, development, and underdevelopment.